Faktor-faktor Risiko Penyakit Jantung Koroner pada Pasien Wanita di Poliklinik Jantung Rumah Sakit dr.Slamet Kabupaten Garut - nugraha, andri (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2018)
Coronary Heart Disease (CHD) is a disease that causes muscle tension in heart caused by the damage in coronary arteries. The incidences of CHD in men are three times greater than in women and it was formerly considered as a disease that mainly attack men. At dr. Slamet Hospital in Garut Regency, the prevalence of CHD in female patients are greater than in male patients. The purpose of this research is to identify the description of the risk factors for the Coronary Heart Disease in female patients at the Cardiology Clinic of dr.Slamet Hospital in Garut Regency. This research is a descriptive research. The sampling technique used was accidental sampling, and the number of samples were 77 patients. The data was obtained through medical records in 2011/2012. The result of the research showed that among 77 respondens, the average age of respondents was 59.86 years, (72.7%) of them had a history of hypertension, (37.7%) of them had a history of diabetes, (75.3%) of them had a history of hyperlipidemia, (63.6%) of them were housewives, (51.9%) of them had a history of oral contraceptives. To reduce the prevalence of CHD in women, it is needed to give health education about CHD, hypertension, diabetes, hyperlipidemia and oral contraceptives.